Healthcare use among immigrants and natives in Sweden on disability pension, before and after changes of regulations. (30th November 2017) - Di Thiene, D; Rahman, S; Helgesson, M; Wang, M; Alexanderson, K; Tiihonen, J; La Torre, G; Mittendorfer-Rutz, E
Abstract: Background: There is limited knowledge regarding psychiatric healthcare utilization around the time of granting disability pension (DP) due to common mental disorders (CMD) among immigrants and if this is related to social insurance regulations. The aim was to evaluate patterns of psychiatric healthcare utilization before and after DP due to CMD among immigrants and natives. A second aim was to evaluate if such patterns differed before and after changes in social insurance regulations in Sweden in 2008. Methods: All 28 354 individuals living in Sweden with incident DP due to CMD, before (2005–06; n = 24 298) or after (2009–10; n = 4056) changes in regulations of granting DP, were included. Patterns of psychiatric in- and specialized outpatient healthcare utilization during a 7-year window around DP granting were assessed by Generalized Estimating Equations estimating multivariate adjusted odds ratios (OR) and 95% confidence intervals (CI). Results: Prevalence rates of psychiatric inpatient care were comparable among immigrants and natives, lower in non-Western immigrants (Africa, Asia and South-America). Three years after DP, non-Western immigrants in comparison to natives and Western immigrants had a stronger decrease in inpatient psychiatric healthcare: OR 0.48 (CI 0.38–0.62), 0.76 (0.70–0.83) and 1.01 (0.76–1.34), respectively. After 2008, a strong reduction in outpatient psychiatric healthcare after DP granting was observed, similarly in immigrants and natives. Conclusions: Non-Western immigrants showed a different pattern of inpatient specialized healthcare after DP granting in comparison to natives. After changes in social insurance regulations, the decline in outpatient psychiatric healthcare following DP granting was comparable in immigrants and natives.